(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Outpatient hysteroscopy is an effective and safe diagnostic and therapeutic method for detecting intrauterine lesions in infertile women, especially in those with suggestive abnormalities or previous assisted reproductive failures. Objectives: To evaluate the outcomes of outpatient hysteroscopy in infertile patients at the National Hospital of Obstetrics and Gynecology. Methods: A descriptive study (combining retrospective and prospective data) was conducted on 149 infertile patients undergoing outpatient hysteroscopy at the National Center for Reproductive Assistance, National Hospital of Obstetrics and Gynecology, from November 2024 to April 2025. Results: The mean age of the study population was 36.1 ± 5.2 years, with 64.4% of patients aged over 35. The median duration of infertility was 3 years (range: 1–28 years). Most patients had no prior intrauterine interventions (81.2%) and no history of uterine surgery (77.9%). Ultrasound detected intrauterine cavity abnormalities in 53.7% of cases (80/149), whereas hysterosalpingography (HSG) identified abnormalities in only 40% (14/35). The indication for diagnostic hysteroscopy is about 40.3%, including consecutive failed preimplantation (35.6%) and recurrent miscarriage (4.7%). Outpatient hysteroscopy confirmed intrauterine pathology in 81.2% of cases, predominantly endometrial polyps (46.3%), endometritis (16.1%), and intrauterine adhesions (18.1%). Interventions during hysteroscopy included polypectomy (46.3%), adhesiolysis of the uterine cavity (18.1%), submucosal myomectomy (1.3%), and endometrial biopsy (2.7%). The median procedure time was 8 minutes (range: 3–30 minutes), with no complications reported. The median volume of saline used was 800 ml (range: 60–3000 ml). Ultrasound showed strong agreement with hysteroscopy in diagnosing polyps (Kappa = 0.824; p < 0.001), whereas HSG demonstrated poor agreement in detecting both polyps and intrauterine adhesions (Kappa < 0.2; p < 0.05). Conclusion: Office hysteroscopy is an effective tool for detecting intrauterine lesions in infertile patients. It allows both diagnosis and intervention in a short duration and is safe for the patient.